An Exploration of the Biological Cognitive Competencies of 10th Grade Science Pupils in the City of Makassar - Adnan (Journal of Biology Education, 2024)
This research is survey research, to determine biology cognitive abilities students in grade X students in the public high schools in Makassar City. The study population was all students of class X science from 23 public high schools in Makassar City in the 2022/2023 academic year. Sample withdrawal was carried out using cluster random sampling and simple random sampling techniques. The total number of research samples was 254 students taken from 8 schools, namely: SMAN 4 Makassar, SMAN 5 Makassar, SMAN 6 Makassar, SMAN 9 Makassar, SMAN 14 Makassar, SMAN 16 Makassar, SMAN 20 Makassar, and SMAN 21 Makassar. The instrument used was 25 items of multiple-choice questions. Data collection was done by distributing tests to students. Data analysis was done descriptively. The results showed that the biology cognitive competencies of class X science pupils at public high school in Makassar City in the low category as of many as 81 people (31.89%), medium category as many as 127 people (50%), high category as many as 31 people (12.2%) and very high category as many as 15 people (5.91%). Based on these results, the cognitive ability of biology class X science students of public senior high school in Makassar City is classified in the medium category.